DEVELOPMENT OF ASSET INVENTORY MANAGEMENT INFORMATION SYSTEM USING THE DELONE AND MCLEAN SUCCESS MODEL APPROACH - Murniasih, Intan; Wiranata, Ade Davy (ISTEK WIDURI, 2024)
Because the number of devices is very large, more than 9000 devices, a tiered process is needed in the distribution of these devices to provide accurate data and smooth distribution. Currently, the device distribution process used by employees is still not good, due to the lack of proper integration and coordination between employees, asset admins, and IT regarding the use and maintenance of these devices. Every year, there is always a system for replacing (updating) employee devices, which causes asset admins and IT to have difficulty in carrying out their tasks, often hindering the device distribution data process and making manual recording an alternative. In this case, manual data recording often gets lost or misplaced and is not recorded in the system. The business process of asset inventory data management is not up-to-date. To improve the existing Asset Inventory Management system, the development of a new web-based asset inventory system is needed, which is expected to assist in the management activities of the company's asset inventory until its implementation. The measurement or testing of the Delone and McLean (2003) success model displays the contribution of the Information System renewal based on the quality dimensions of the updated model. Based on the analysis results, the data is classified into five main categories: Very Good (84.01% - 100%), Good (68.01% - 84.00%), Fair (52.01% - 68.00%), Poor (36.01% - 52.00%), and Very Poor (20.00% - 36.00%). This classification provides a clear picture of the distribution of values or performance, making it possible to evaluate and identify the level of success or the need for improvement in various analyzed aspects. Thus, this table serves as a guide in prioritizing and making data-based decisions.ABSTRAKKarena jumlah perangkat yang sangat besar lebih dari 9000 perangkat, membutuhkan tingkatan proses dalam pendistribusian perangkat – perangkat tersebut untuk menyajikan data yang akurat dan kelancaran pendistribusian perangkat. Pada saat ini, proses pendistribusian perangkat yang digunakan oleh karyawan masih kurang baik, karena masih kurangnya kordinasi yang belum terintegrasi secara benar antara karyawan, Admin aset, IT mengenai penggunaan dan pemeliharaan perangkat tersebut. Dalam setiap tahunya selalu terjadi sistem pergantian perangkat (pembaharuan perangkat) karyawan, Hal ini mengakibatkan admin aset dan IT kesulitan dalam melaksanakan pekerjaanya, sehingga sering terhambat dalam proses pendataan distribusi perangkat dan menjadikan pencatatan manual menjadi alternatifnya. Dalam hal ini pendataan yang manual sering kali hilang atau terselip dan belum tercatat disistem. Proses bisnis pendataan persediaan asset yang kurang terupdate. Untuk memperbaiki proyak sistem Asset Inventory Management yang sudah berjalan selama ini dibutuhkan pengembangan sistem asset inventory yang baru berbasis website, yang diharapkan mampu membantu aktivitas pengelolaan Asset inventory perusahaan sampai dengan implementasinya. Pengukuran atau pengujian model kesuksesan Delone and McLean (2003), menampilkan kontribusi pembaharuan Sistem Informasi berdasarkan dimensi kualitas model yang diperbaharui. Berdasarkan hasil analisis, data diklasifikasikan ke dalam lima kategori utama, yaitu Sangat Baik (84,01% - 100%), Baik (68,01% - 84,00%), Cukup (52,01% - 68,00%), Kurang (36,01% - 52,00%), dan Sangat Kurang (20,00% - 36,00%). Klasifikasi ini memberikan gambaran yang jelas tentang distribusi nilai atau performa, sehingga dapat digunakan untuk mengevaluasi dan mengidentifikasi tingkat keberhasilan atau kebutuhan perbaikan dalam berbagai aspek yang dianalisis. Dengan demikian, tabel ini berfungsi sebagai panduan dalam penentuan prioritas dan pengambilan keputusan berbasis data.